Effect of small-interfering RNA (As1974) and HFq-binding proteins on resistance gene and host microRNA (miR-30C) expression in Pseudomonas aeruginosa-infected patients from Iraq - Al fatlah, Bashaer Saad Jabbar; Bunyan, Ilham Abbass; Al Husseini, Rafid Fakher Hussein (Medical Journal of Babylon, 2023)
Abstract Background: MicroRNAs (miRNAs) are a class of small RNAs encoded by the genome that regulate the production of cellular mRNAs that include either incomplete or complete miRNA-binding sites. Objectives: To evaluate the impact of sRNA (As1974) and HFq-binding proteins on the expression of resistance gene and host miRNA (miR-30C) in Iraqi urinary tract infections (UTIs) patients infected with Pseudomonas aeruginosa. Materials and Methods: Patients with UTIs from Baghdad, Iraq's Baghdad Teaching Hospital, Ghazi Hariri Hospital, Central Laboratories in Medical City, and Al-Yarmouk Hospital were recruited during June 2022 and October 2022 to provide 200 clinical samples. Results: Out of 200 patients with UTIs, only 56 (38.14%) were diagnosed as P. aeruginosa from positive urine samples. Urine samples were analyzed for HFQ gene expression, and the results showed that HFQ is overexpressed in P. aeruginosa-resistant samples compared to sensitive clinical samples, as measured by fold change after normalization with housekeeping gene 16sRNA by folding (21.4971.241 vs. 1.92142 0.04598). Furthermore, normalization of As1974 gene expression in urine samples using 16sRNA revealed a downregulation of As1974 in resistance, with a fold change of 0.66220.0465 versus 2.0121.0243. The miR-30 gene was shown to be downregulated in urine and blood samples (1.360.34, 0.478210.03678) as compared to those of healthy subjects. Conclusions: All ages were susceptible to the UTIs, also females suffered from UTIs more than males. A significant over expression of HFQ-binding protein in P. aeruginosa compared to sensitive clinical samples. Downregulation of As1974 in resistance.